Descriptive Text Writing Skills Through Picture Media in Elementary School Students - Fitrianingsih, Rina Ayu; Suaedi, Hasan; Vardani, Eka Nova Ali (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study aimed to describe the skills of writing descriptive text through image media in the form of identification structures or general statements and section description structures in class VII students at SMP Negeri 2 Genteng. The research data is in the form of essays/the results of learning the skills of writing descriptive text through the media of images in class VII B students at SMP Negeri 2 Genteng. Data collection techniques used documentation techniques which were carried out through five stages, namely (1) research questions, (2) determining category definitions and levels of abstraction, (3) category formulation, (4) category revision, and (5) final work. The research instrument is the researcher himself as the main instrument and is assisted by supporting instruments in the form of assessment instrument tables. The data in the study were analyzed through four stages, namely: (1) reading and studying, (2) identifying, (3) presenting the results of the categorization, and (4) concluding the results of the analysis found. The technique for testing the validity of the data in this study uses the observation persistence technique. The results of the data analysis show that there are assessment indicators in the form of (1) identification structures or general statements which include object recognition. (2) the structure of the description of the part, which includes words that refer to the names of objects, material or action verbs, and adjectives. Based on the data results, this study concludes that students are categorized as good because students can write descriptive text through media images based on assessment indicators.